Phytoremediation of Aquiculture Wastewater by Azolla Pinnata - Nur Hafeezah Md Adnan (2018)
The development of aquaculture activities is one of the fastest growing sectors of agriculture. Despite of the generation of economic in aquaculture industry, the activity may also degrade the environmental quality. In this study, phytoremediation technology was applied as the alternative to remediate the contaminant such as heavy metal and non-metal in the UMK Jeli Tilapia ﬁsh pond. The phytoremediation mechanism was carried out by the aquatic plant known as Azolla pinnata. The research was aimed to determine the removal efficiency of parameter elements and regulation of physic-chemical parameter (pH, DO and TDS) in aquaculture wastewater by Azolla pinnata. Besides, the accumulation of parameter elements within Azolla pinnata was also evaluated. 1n the constructed wetland, three set of reactor tanks with plant samples and one control tank without plant samples were ﬁlled with aquaculture wastewater to undergo phytoremediation for 2 days for each of the 6 cycles. All the samples were analysed by the X-Ray Fluorescence (XRF) Spectrometer and YS1 Multi Probe System (MPS) to identify the concentration of each pollutant in the water and determine the physico-chemical parameters changes. Based on the result calculated by Microsoft Excel 2010, the physico-chemical analysis showed that Azolla pinnata could decrease pH, DO, and maintain the TDS. Plus, the plant proved its ability to remove Al, Mg, Ba, Sb, S, and P by 35.2 1 47.2, 43.2 1 49.6, 19.6 1 17.3, 32.5 , 29.1, 12. 3 + 12.8, 1.7 +2.8 respectively. Furthermore, A. pinnata can accumulate the signiﬁcant elements in plant tissue. The maximum BCF was recorded on Fe with 520.79 mg/L proving that the plant (Azolla pinnata) could remove Fe through the phytoremediation mechanism.